(3CSdGc GdLhgQ aj fXe eLOO GdbQf GdKGdK YTQ TjN GdESdGe eMeO Hf Ydi GdThcGfis - (3, eMeO Hf Ydj Hf eMeO Hf YHO Gddg, CHh YHO Gddg GdThcGfj , J (B1250 (3g` s ((3jQje HGdjef s)
(3ChdgG (B:s
(3ef MQa GdgeRI bhdg (B: (3OYi dhei Ydi aQW GdghGA hOGhi Ef bOQJ Ydi GdOhGA s
(3BNQgG (B:s
(3BNQg ef MQa GdjGA bhdg (B: (3hce YhO Gddg GdLejd aaQL GdNWhH hbO cGfJ JTjH GdfhGUjG gPG eG Cecf LeYg s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQ eQJH Ydi GdMQha GdCHLOjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf GHQGgje GdYjRQi s
Keywords: (3GdCOHs